1996
DOI: 10.1128/jvi.70.7.4538-4548.1996
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive phosphorylation of the vesicular stomatitis virus P protein modulates polymerase complex formation but is not essential for transcription or replication

Abstract: As a subunit of both the P-L polymerase complex and the P-N assembly complex, the vesicular stomatitis virus (VSV) P protein plays a pivotal role in transcription and replication of the viral genome. Constitutive phosphorylation of this protein is currently thought to be essential for formation of the P-L complex. We recently identified the three relevant phosphate acceptor sites in the VSV Indiana serotype P protein (R. L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 32 publications
3
23
1
Order By: Relevance
“…From the results documented here, we conclude that although phosphorylation of P protein in the domain I residues is not essential for replication function of the protein, this modification is critical for its transcriptional activity. Using a similar panel of mutant P proteins, Spadafora et al recently concluded that phosphorylation of the domain I residues of the Indiana serotype P protein does not play a major role in DI RNA replication in vivo (50). Our results presented in this report confirm their results of in vivo DI RNA replication studies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…From the results documented here, we conclude that although phosphorylation of P protein in the domain I residues is not essential for replication function of the protein, this modification is critical for its transcriptional activity. Using a similar panel of mutant P proteins, Spadafora et al recently concluded that phosphorylation of the domain I residues of the Indiana serotype P protein does not play a major role in DI RNA replication in vivo (50). Our results presented in this report confirm their results of in vivo DI RNA replication studies.…”
Section: Discussionsupporting
confidence: 88%
“…Further increase in the amount of P 60/62/64 plasmid in transfection did not result in increased levels of transcription (data not shown). It should noted that with increasing amounts of the plasmid transfected (up to 9 g), a corresponding increase in the P-protein expression was observed (data not shown), which is consistent with our previous observation (46) and those obtained recently by Spadafora et al (50).…”
Section: Expression and Stability Of Wt And Mutant P Proteins In Transupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, D70 is present in a region of VSV-P that is heavily phosphorylated (phosphorylation of residues 60, 62 and 64 has been described) (51). Phosphorylation of these sites has been proposed to be important in P-protein dimerization and interaction with the L-protein (large polymerase protein) (5256) and phosphorylation of this region is essential for functional RNA dependent RNA polymerase activity (57). Because tyrosine residues are known to be phosphorylated in the VSV-P protein (58), it is therefore tempting to speculate that a tyrosine at position 70 could be phosphorylated, and that this phosphorylation somehow overcomes the block mediated by TRIM69.…”
Section: Discussionmentioning
confidence: 99%